Evaluasi Keragaan Tujuh Genotipe Cabai (Capsicum annuum L.) di Lahan Gambut - Saputra, Mico; ', Idwar; ', Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of this research was to evaluate variability seven genotype chili (Capsicum annuum L.) in peatlands and find genotype that have high             yield. Research arranged in a randomized block design consisting of seven treatments (genotype C-5, C-111, C-120, C-159, C-159 x C-5, C-159 x C-111,   C-159 x C-120) with three replications. Parameters measured were flowering date, harvesting date, plant height, height dichotomous, stem diameter, canopy width, fruit length, fruit diameter, weight per fruit, total weight per plant. The results showed that seven genotipe chili planted variability in peatlands visible between genotype, especially in stem diameter, fruit length, fruit diameter, flowering date, weight per fruit and fruit weight per plant. Genotype C-5 which is a great chili has the highest yield with weight per fruit 13,78 g and total weight per plant 407,02 g. Keywords : Chili, evaluation, genotype, peatland and yield.